Pendapatan dan Tingkat Kesejahteraan Rumah Tangga Petani Tembakau di Desa Sukasari, Kecamatan Sukasari, Kabupaten Sumedang - Edi Gunawan Saputra; Trisna Insan Noor (Universitas Galuh, 2026)
Sumedang Regency is the second-largest tobacco-producing region in West Java. Currently, the tobacco commodity in Sumedang Regency is facing challenges related to declining production and increasing fertilizer prices. Sukasari Village is one of the main tobacco production centers in Sumedang Regency, where the majority of residents work as tobacco farmers. This study aims to identify household income, analyze the structure of household expenditure, and measure the level of household welfare. The research employs a descriptive quantitative approach. The data were processed quantitatively, and the results were presented descriptively. The results of the study show that farmers’ annual household income amounts to IDR 38.295.939, consisting of income from tobacco farming IDR 32.338.806/year, non-tobacco farming IDR 940.633/year, off-farm IDR 976.667/year, non-farm IDR 4.039.833/year. Additional income from family members includes wives’ income and children’s income IDR 2.448.000/year. Total household expenditure reaches IDR 39.442.262/year, comprising food expenditure of IDR 26.891.300/year and non-food expenditure of IDR 12.550.963/year. The welfare level of farmers’ households falls under the high welfare category. Income derived from tobacco farming serves as the primary source of household income for farmers. Food expenditure constitutes the largest portion of total spending, and farmers’ households are in a condition of food insecurity. Overall, the farmers’ households are at a high level of livelihood feasibility.